Financial Benefit Analysis of an Electric Water Heater with Direct Load Control in Demand Response - Ahmed, MT (2021)
The peak demand reduction during peak hour is a challenge to the retail energy providers. Demand response program plays a major role to fulfil this purpose. The small household appliances like electric water heater can participate in the demand response program by aggregating it in the smart building energy management system. This paper discusses demand response possibilities of a residential electric water heater, the overall consumption profile, temperature profile and the financial benefit in the consumer level. The direct load control demand response method in yearly timeframe is proposed and applied. Realtime electricity pricing with incentive-based demand response is considered and applied to the direct load control with financial benefit to the consumers. The study includes the difference between normal consumption and consumption after using DLC, normal temperature profile and temperature profiling after DLC. The results exhibit that there is significant energy consumption reduction in the consumer level without making any discomfort.